A clinical trial on the acute effects of methadone and buprenorphine on actual driving and cognitive function of healthy volunteers. Issue 2 (18th December 2018) - Strand, Maren Cecilie; Vindenes, Vigdis; Gjerde, Hallvard; Mørland, Jørg Gustav; Ramaekers, Johannes G.
Abstract : Aims: The present study assessed the acute effects of methadone and buprenorphine on actual on‐road driving performance and neurocognitive function. Methods: Methadone (5 and 10 mg per os) and buprenorphine (0.2 and 0.4 mg sublingual) were administered to 22 healthy volunteers in a five‐way, double‐blind, randomized, placebo‐controlled, double‐dummy, cross‐over study. Driving performance was assessed with an on‐road driving test. The primary outcome measure was standard deviation of lateral position (SDLP), a measure of road tracking control. Laboratory tests were used to measure cognitive function (e.g. reaction time and attention) and questionnaires were used to assess subjective measures of mood and sedation. Results: There was no significant main effect of treatment on SDLP. Yet, analysis of individual drug‐placebo contrast data revealed that buprenorphine 0.4 mg significantly increased SDLP. Driving impairment was mild and below the impairment threshold of a blood alcohol concentration of 0.5 mg ml −1 . Four participants stopped their driving test while under the influence of either opioid due to sleepiness. Both opioids produced impairments of cognitive task performance and increased sleepiness particularly at the highest dose. Conclusions: Analgesic doses of buprenorphine produced mild impairing effects on driving and related cognitive skills, while methadone impaired cognitive task performance but not driving performance. Large individual variations were observed for both drugs. Patients should be informed about the possibility of driving impairment when initiating opioid treatment.